2021
DOI: 10.3390/life11050433
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Parameters in Near-Infrared Fluorescence Imaging with Indocyanine Green: A Systematic Review of the Literature

Abstract: (1) Background: Near-infrared fluorescence imaging is a technique capable of assessing tissue perfusion and has been adopted in various fields including plastic surgery, vascular surgery, coronary arterial disease, and gastrointestinal surgery. While the usefulness of this technique has been broadly explored, there is a large variety in the calculation of perfusion parameters. In this systematic review, we aim to provide a detailed overview of current perfusion parameters, and determine the perfusion parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…While in the field of autofluorescence and LSCI attention is paid to the quantification of the signal, this is not yet the case with ICG-angiography in total thyroidectomy. However, in other areas of interest, reviews on ICG-angiography concluded that time-related perfusion parameters, such as inflow parameters, provide a better predictive value for postoperative outcomes than the absolute fluorescence intensity [ 83 , 84 ]. The absolute fluorescence intensity was found to be strongly influenced by factors like the plasma ICG concentration, the amount of ambient light, the camera-to-wound bed distance, and the angle of the camera relative to the wound bed [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…While in the field of autofluorescence and LSCI attention is paid to the quantification of the signal, this is not yet the case with ICG-angiography in total thyroidectomy. However, in other areas of interest, reviews on ICG-angiography concluded that time-related perfusion parameters, such as inflow parameters, provide a better predictive value for postoperative outcomes than the absolute fluorescence intensity [ 83 , 84 ]. The absolute fluorescence intensity was found to be strongly influenced by factors like the plasma ICG concentration, the amount of ambient light, the camera-to-wound bed distance, and the angle of the camera relative to the wound bed [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was a widespread distribution of measured intensity over time in both groups. There are several earlier studies reporting the use of ICG NIR fluorescence imaging for perfusion assessment in patients with LEAD as well as control patients [7,16,18,[20][21][22][23][24][25]. In these studies, an abundance of parameters has been examined, which have been compared to varying diagnosis measurements, including ABI, TP, and transcutaneous oxygen pressure measurements.…”
Section: Discussionmentioning
confidence: 99%
“…To date, unfortunately only a few studies have demonstrated a direct correlation between visualization and glandular perfusion and a reduction in hypoparathyroidism [30], which is in any case limited to the temporary but not definitive form. Moreover, none of the prevention methods adopted seem to be able to reduce hypocalcaemia [42,[49][50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%